Virtual Museum in the Metaverse: An educational experience on History and Racism in Nursing (Research, Society and Development, 2026)
Objective: To develop an innovative educational proposal using the metaverse to promote an immersive and reflective experience on the history of nursing and its historical challenges. The initiative aimed to expand students understanding of the role of Black women in the profession, highlighting the intersectionality between technology, education, and social empowerment. Method: This study is characterized as an experience report conducted in a technical nursing program in the interior of the state of São Paulo, Brazil. The experience involved four face-to-face sessions totaling 14 hours, during which students explored a virtual museum, interacted with historical content, and participated in gamified activities. Tools such as Spatial.io and Ready Player Me were used to create virtual environments and avatars, providing an accessible and interactive educational experience. Results: The findings demonstrated that the use of the metaverse enhanced learning and promoted critical reflections on inclusion, racism, and professional identity. Conclusion: Digital immersion is a strategy capable of integrating pedagogical sensitivity and technology, making teaching more dynamic and inclusive.